The Uniqueness of Islamic Economic and Financial Practices in Indonesia - Azharsyah Ibrahim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This issue highlights the global progress made against Covid-19 over the past three years. It predominantly publishes articles on Islamic economics and finance, showcasing unique practices throughout Indonesia, including accounting, the zakat system, halal tourism, Islamic banking, the capital market, and microeconomics. As customary, all articles have undergone double-blind peer reviews by relevant experts. Some articles required multiple rounds of review before acceptance, while others were accepted after a single round. The decisions heavily relied on the feedback provided by the reviewers. Based on that, we have selected the top 13 papers to present to you, and we are confident that each one stands out in its own unique manner.